2020
DOI: 10.1097/cad.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the cytotoxic activity of two novel digitoxigenin analogues on H460 lung cancer cells

Abstract: Cardiac glycosides (CGs) are natural compounds traditionally used for the treatment of heart disorders, and recently new therapeutic possibilities were proposed. Their antitumor reports and clinical trials have notably enhanced, including those targeted for lung cancer, the most lethal type that lacks of new treatment agents, instigating the research of these molecules. The CGs studied here, named C10 {3β-[(N-(2-hydroxyethyl)aminoacetyl]amino-3-deoxydigitoxigenin} and C18 (3β-(aminoacetyl)amino-3-deoxydigitoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Even clinical trials for the treatment of cancer have begun using some cardiac glycosides or their derivatives. 15,44 Anvirzel, a water extract from oleander, was the first cardiac glycoside examined in an anticancer clinical study and showed substantial anticancer action against a variety of malignancies with few side effects. [45][46][47] Cardiac glycosides isolated from Thevetia peruviana (Pers.)…”
Section: Cytotoxic Activity Of Cardiac Glycosides Identified In Afric...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even clinical trials for the treatment of cancer have begun using some cardiac glycosides or their derivatives. 15,44 Anvirzel, a water extract from oleander, was the first cardiac glycoside examined in an anticancer clinical study and showed substantial anticancer action against a variety of malignancies with few side effects. [45][46][47] Cardiac glycosides isolated from Thevetia peruviana (Pers.)…”
Section: Cytotoxic Activity Of Cardiac Glycosides Identified In Afric...mentioning
confidence: 99%
“…All cardiac glycosides contain a steroid ring connected to an unsaturated lactone ring in position 17, and many of them are related to a sugar moiety in position 3 as well. 15,16 This review on cardiac glycosides isolated from the African region will help broaden the scope of the importance of this secondary metabolite. It will also encourage further research into their isolation with great pharmacological activities, leading to drug discovery and development in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these compounds induced autophagic cell death by attenuating the PI3K/AKT/mTOR signaling pathway through the inhibition of mTOR, LC3, Beclin 1, PI3K, and p62 genes [ 15 , 126 , 127 ]. Recently, Boff et al [ 143 ] demonstrated the cytotoxic effect of semisynthetic C10 and C18 digitoxigenin analogs on H460 lung cancer cells. Both the compounds demonstrated high cytotoxicity as they induced apoptotic activity and reduced the cellular viability of H460 cells.…”
Section: Cardiac Glycosides As Cancer Therapeuticsmentioning
confidence: 99%
“…8 CGs also inhibit testosterone production via the attenuation of cAMP accumulation, activities of adenylyl cyclase and cytochrome P450 scc in rat testicular cells [9][10][11] and progesterone release by rat granulosa cells via a Na + , K + -ATPaseindependent mechanism involving the inhibition of post-cAMP pathway cytochrome P450 scc and the protein function of steroidogenic acute regulatory (StAR) protein. 12 CGs have been known to possess anticancer effects in endocrine-related cancers comprising lung cancer, 13 prostate cancer, [14][15][16][17] and breast cancer 18 through inhibiting the cell migration 19 and proliferation and inducing apoptosis. 20,21 CG induces cell apoptosis in MCF-7 (estrogen receptor positive-breast cancer cell line) and MDA-MB-468 (triplenegative breast cancer) through arresting the G 0 /G 1 phase.…”
Section: Introductionmentioning
confidence: 99%